Social, economic, environmental and political constraints on municipal fiscal policy: Do tough national sanctions act as a fire blanket or an oxygen tent? - Houlberg, Kurt (Politica, 2018)
The impact of local social, economic, environmental and political constraints (SEEP) on local government policy has long been a central theme of the decentralization and local government literature. How do local SEEP factors affect the fiscal management of Danish municipalities after a major structural reform in 2007? Does a tough sanction-based expenditure limitation regime affect the relationship between local external constraints and municipal fiscal policy? The fiscal management of Danish municipalities has improved significantly after the economic crisis and a sanction regime implemented by the national government in 2011. This empirical analysis shows that economic constraints and especially changes in economic constraints significantly affect the fiscal policy but that also environmental instability in terms of population changes make it harder to balance the budget. In addition, a sanction regime seems to place constraints on local authorities’ fiscal management policy, which reduces the importance of environmental factors.